Análisis de los riesgos psicosociales en la central de generación hidráulica " Península " de la Empresa Eléctrica Ambato durante el período 2009-2010 y propuesta de un plan de capacitación en prevención de estrés laboral. - Viteri Ojeda, Julio Gilberto (2011)
Psychosocial risks are present all work activity, logically are present in Central Hydroelectric Generation Península of Ambato Electric Company, this is the reason why it is important that all contributors to this area have knowledge and made aware of the risks they are exposed in their daily activities. Specific objectives allow us to demonstrate that psychosocial risk factors affect occupational health of the operators of hydroelectric generation and therefore the quality of life, for them to use the method Lest. Being in full knowledge that psychosocial risk is present in any task that involves the individual reacts with character altered responses psychosocial responses, physiological and behavioral, that can have immediate consequences as the appearance of occupational diseases occasions by occupational stress. The methodology used is basically bibliographical, documentary, descriptive, field and observation that allows us to verify onsite the execution of daily activities and determine the factors that cause low productivity of workers. The lack of knowledge in aspects of psychosocial risks in the future will have an impact with a significantly influence on the mental load of a collaborator in a given job, as also the development of occupational diseases to the damage of themselves and the company.